(untitled) (Bangladesh Journal of Public Administration, 2022)
Dhaka offers an exceptional context for metro rail services with the world’s highest population density. How the sociocultural condition of the city’s population would affect the future ridership of the under-construction Dhaka metro rail is an interesting question. This paper aims to shed some light on this issue. It uses the quantitative data collected through a heuristically designed survey questionnaire by the participants of a training programme designed for the Dhaka Mass Transit Company Limited officials and implemented by the Bangladesh Public Administration Training Centre. It presents the survey findings from 625 prospective metro rail service users from six catchment areas of the Mass Rapid Transit (MRT) Line-6 using descriptive and inferential statistics. Contradicting the previous research findings of other contexts, the variables of walkable footpaths, transfer services, and commercial space in stations appeared as non-significant predictors of metro ridership in a regression analysis. A new suggested variable of female coaches in the metro rail also was found non-significant, contradicting local conventional beliefs. On the other hand, strap-hanging, reliability, timeliness were positively, and the fare of metro travel was negatively significant at p<.05, though all of them showed minimal impact on ridership. The findings imply that males and females will travel by the metro rail in the same coach, even standing. However, the fare of metro travel can become a crucial factor for travel decisions, which carries policy implications for the metro rail authority. These findings contribute to the scientific knowledge of urban transportation governance regarding rapid-transit facility development.